2013
DOI: 10.1186/1471-2458-13-1006
|View full text |Cite
|
Sign up to set email alerts
|

Use of different subjective health indicators to assess health inequalities in an urban immigrant population in north-western Italy: a cross-sectional study

Abstract: BackgroundDespite the steady growth of the immigrant population in Italy, data on the health status of immigrants are scarce. Our main goals were to measure Health-Related Quality of Life (HRQoL), Self-Rated Health (SRH) and morbidity among immigrants in Genoa. We aimed to assess the relative contribution of some social, structural and behavioral determinants to “within-group” health disparities.MethodsWe enrolled 502 subjects by means of snowball sampling. The SF-12 questionnaire, integrated with socio-demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 76 publications
1
11
0
3
Order By: Relevance
“…Our data only showed a statistically significant difference for 45- to 64-year-old males, however. To our knowledge, no estimates of the prevalence of CHF among immigrants are available in the literature, but if we consider the broader category of heart disease, several studies have reported that immigrants have lower mortality rates of heart disease than native populations [ 21 ], which are findings consistent with the “healthy migrant” effect already seen for other diseases [ 22 ].…”
Section: Discussionsupporting
confidence: 63%
“…Our data only showed a statistically significant difference for 45- to 64-year-old males, however. To our knowledge, no estimates of the prevalence of CHF among immigrants are available in the literature, but if we consider the broader category of heart disease, several studies have reported that immigrants have lower mortality rates of heart disease than native populations [ 21 ], which are findings consistent with the “healthy migrant” effect already seen for other diseases [ 22 ].…”
Section: Discussionsupporting
confidence: 63%
“…There are some limitations to our study that need to be considered when interpreting our results. First, although the SF-36, the parent questionnaire for the SF-12, and the SF-12 itself are widely used valid instruments that have been previously used to measure HRQOL including immigrants [ 1 , 2 , 6 , 12 , 23 ], measurement bias might have been occurred by the blending of health and physical and mental function concepts in the SF-36 [ 24 , 25 ]. As our study focused on the physical and mental health summary scores, it could still be possible that ethnicity affected HRQOL independently of physical and mental functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Existing research output focuses disproportionately on a few categories of migrants and health concerns, and on migration to and from high-income countries(9)(10) (11) (12). In Italy, female immigrants are at greater risk of receiving inadequate healthcare services and poor quality outcomes during their pregnancy and delivery compared to native females (13). These studies demonstrate that migrants are more likely to use modern contraception and antenatal care than non-migrants.…”
Section: Introductionmentioning
confidence: 75%